Microstructural engineering of high-content rubber asphalt via precision devulcanization for enhanced performance - Yang, Meng; Li, Shanyuan; Guo, Xiaohong; Pu, Mingyan; Li, Chongyuan; Xu, Ouyang; Wu, Shibing; Jiang, Chaozhe; Li, Yukun; Mao, Hanqing; Zhong, Lei; A, Wenqian (Frontiers in Materials, 2025)
IntroductionThe practical deployment of high-content rubberized asphalt is often hindered by its compromised workability and unstable performance. Moving beyond conventional devulcanization approaches, this study introduces an integrated strategy of interface-controlled devulcanization and microstructural tailoring to address these challenges.MethodsA bespoke devulcanizing agent (RubberSynth-AP) was synthesized to promote selective scission of sulfur-based crosslinks and improve interfacial adhesion. Coupled with an optimized production process, this method allows the stable integration of crumb rubber at concentrations up to 30% by binder weight. Multi-scale rheological analyses—encompassing temperature sweeps, multiple stress creep recovery (MSCR), and linear amplitude sweep (LAS) tests—were employed.ResultsAn optimum rubber content of 26% was identified, exhibiting a superior combination of properties: a failure temperature of 76.5 °C, 40% lower viscosity, 53.12% recovery rate, and enhanced fatigue resistance. Mechanistic analysis uncovered a microstructural evolution from a heterogeneous, stress-concentrating system to a homogeneous, elastic-network-dominated morphology. This structural improvement supported the adoption of a dense-graded AC-13 mixture design, achieving a remarkable dynamic stability of 3,850 cycles/mm. Economically and environmentally, this technique promotes the consumption of 18 tons of waste rubber per lane-kilometer with a cost reduction of approximately ¥17,000.DiscussionCollectively, this study demonstrates that the interface-controlled devulcanization strategy enables the production of high-content rubberized asphalt (up to 30%) with superior and balanced rheological properties, overcoming the longstanding workability-performance trade-off. The findings provide a scientifically-grounded and economically viable solution for developing sustainable pavement materials.